2021
DOI: 10.1080/00207144.2021.1836934
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotizability: Emerging Perspectives and Research

Abstract: Hypnotizability refers to "An individual's ability to experience suggested alterations in physiology, sensations, emotions, thoughts, or behavior during hypnosis" (Elkins, Barabasz, Council, & Spiegel, 2015). Research has demonstrated that most people are hypnotizable and that individual differences in hypnotizability exist. In recent years, there have been important advances on perspectives and new, well-validated scales for measurement that seek to improve on older measurement instruments. Emerging research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…People who are more hypnotisable understandably experience a greater effect or have a quicker response to hypnotherapy, whereas those lower in hypnotisability may need more sessions to achieve a similar response or the clinician may need to experiment with a wider range of hypnosis techniques (Elkins 2015). Elkins (2021) challenges the validity of the HIP as an assessment of hypnotisability and concludes that an improved formal assessment of hypnotisability will lead to better clinical research outcomes and integration into hypnosis intervention protocols.…”
Section: Hypnotherapy and Hypnotisabilitymentioning
confidence: 99%
“…People who are more hypnotisable understandably experience a greater effect or have a quicker response to hypnotherapy, whereas those lower in hypnotisability may need more sessions to achieve a similar response or the clinician may need to experiment with a wider range of hypnosis techniques (Elkins 2015). Elkins (2021) challenges the validity of the HIP as an assessment of hypnotisability and concludes that an improved formal assessment of hypnotisability will lead to better clinical research outcomes and integration into hypnosis intervention protocols.…”
Section: Hypnotherapy and Hypnotisabilitymentioning
confidence: 99%
“…In sum, explicit training of hypnotizability appears to be possible. For individuals of low hypnotizability, it might even merely require more experience (e.g., more hypnotic sessions) to improve their ability to respond to hypnotic suggestions ( Elkins, 2021 ). For example, Kaczmarska et al (2020) reported improvements in hypnotizability after a minimum of three sessions of hypnotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…There are mentions of a high correlation between the scores for the self-rating scales of the hypnosis depth and the scores for the scales of hypnotizability (Szabó, 1993;Tart, 1978), as well as the degree of the particular components that the hypnotic state includes (such as absorption or dissociation) and hypnotizability (Facco et al, 2017;Frischolz et al, 2015). The last one many studies indicate to be a stable characteristic of an individual (Elkins, 2021;Oakley & Halligan, 2013). This also leads to the methods of a subjects' hypnotizability assessment with scales, where the more complex suggestion they can perform (in other words, the deeper they can go into trance), the more hypnotizable they are.…”
Section: Introductionmentioning
confidence: 99%
“…One of the differences between the procedures by which hypnosis is researched, compared with when it is applied in therapeutic settings, is whether or not hypnotizability is assessed. When researching the nature of hypnosis, it is common practice to include the use of a hypnotizability scale (Elkins, 2021). In contrast, it is very much the exception to find scales being used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation